XX АСРНИНГ 50-60 ЙИЛЛАРИДА ИСЛОМ МУАССАСАЛАРИ ФАОЛИЯТИНИ СОВЕТ ҲОКИМИЯТИ ТОМОНИДАН ЧЕКЛАШ СИЁСАТИ ВА УНИНГ ОҚИБАТЛАРИ (ФАРҒОНА ВИЛОЯТИ МИСОЛИДА) (Scientific journal of the Fergana State University, 2023)
In this article the activities of Muslim religious institutions and organizations of Fergana valley (1950-1960 years) on the base of scientific evidence are researched.